2021
DOI: 10.4254/wjh.v13.i10.1208
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive real-time assessment of hepatic macrovesicular steatosis in liver donors: Hypothesis, design and proof-of-concept study

Abstract: Macrovesicular Steatosis (MS) is an independent risk factor for adverse post-liver transplant (LT) outcomes. The degree of MS is intimately related to the viability of the liver graft, which in turn is crucial to the success of the operation. An ideal liver graft should have no MS and most centres would find it unacceptable to use a donor liver with severe MS for LT. While a formal liver biopsy is the gold-standard diagnostic test for MS, given the logistical and time constraints it is not universally feasible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Liver specimens were evaluated by hematoxylin and eosin staining using either frozen or permanent section. Macrovesicular steatosis was defined as a single vacuole larger than the nucleus, replacing most of the hepatocyte cytoplasm and displacing the nucleus to the cell membrane[ 27 ]. Macrosteatosis was categorized as no steatosis (< 5%), mild steatosis (10%-29%), moderate steatosis (30%-60%), and severe steatosis (> 60%)[ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Liver specimens were evaluated by hematoxylin and eosin staining using either frozen or permanent section. Macrovesicular steatosis was defined as a single vacuole larger than the nucleus, replacing most of the hepatocyte cytoplasm and displacing the nucleus to the cell membrane[ 27 ]. Macrosteatosis was categorized as no steatosis (< 5%), mild steatosis (10%-29%), moderate steatosis (30%-60%), and severe steatosis (> 60%)[ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Surgical experience with macroscopic liver assessments therefore still plays an important role in supporting decision making, while machine perfusion (MP) techniques are explored to identify more reliable markers for viability assessments. New techniques to quantify the fat in the entire organ are currently being explored, including MRI and spectroscopy [ 78 , 79 ]. A large study with 20,000 transplants from the US and Europe demonstrated the safe use of microsteatotic grafts for recipients of all risk levels, according to the balance of risk (BAR) score [ 15 ].…”
Section: Types Of Extended Criteria Donor Livers and Associated Risk ...mentioning
confidence: 99%